2013
DOI: 10.5539/jsd.v6n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition Among Under-Five Children in Two Fishing Communities in Mafia Island Marine Park, Tanzania

Abstract: Undernutrition and food insecurity are critical problems among under-five children in many developing countries. This study was carried out for eight months between 2009 and 2011. It combined quantitative data (N=156) and qualitative data to explore nutritional status among under-five children in Jibondo and Chole villages within Mafia Island Marine Park in Tanzania. Weight-for-age analysis was performed according to World Health Organization standards to determine the proportion of underweight children among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…However, following their engagement in seaweed culture, middle-aged women at Jibondo were found to be financially stronger than some of the men and the interviewed female household heads revealed that they met their basic needs without assistance. This undermined women's capacity to carry out their role in children's upbringing and well-being, although it may also suggest an important role played by women in sustaining life at Jibondo (Hauzer et al, 2013;Moshy et al, 2013). However, women were cautious to reveal their actual earnings to their spouses, in trying to avoid being made to shoulder household maintenance or in fear of men using their income for personal interests such as paying bride price for another wife.…”
Section: Economic Situationsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, following their engagement in seaweed culture, middle-aged women at Jibondo were found to be financially stronger than some of the men and the interviewed female household heads revealed that they met their basic needs without assistance. This undermined women's capacity to carry out their role in children's upbringing and well-being, although it may also suggest an important role played by women in sustaining life at Jibondo (Hauzer et al, 2013;Moshy et al, 2013). However, women were cautious to reveal their actual earnings to their spouses, in trying to avoid being made to shoulder household maintenance or in fear of men using their income for personal interests such as paying bride price for another wife.…”
Section: Economic Situationsmentioning
confidence: 86%
“…MIMP SESs is in a relatively good condition (Baker, 2013;URT, 2011), which is desired by conservationists, government and tourism operators, while the social part experience poor and undesired conditions (Benjaminsen and Bryceson, 2012;Moshy et al, 2013;Mwaipopo, 2008;Walley, 2004). Although park authorities are urged to ensure that the needs of resource-dependent communities are met (Marshall et al 2009), the real challenges of day-to-day life within the MIMP have resulted in increased hardship and poverty.…”
Section: Forum For Development Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also argued that since the introduction of jeans clothing, men do not go to farms after they returned from fishing trips. Moshy, Masenge, and Bryceson (2013) also found that, men spent nonfishing time visiting the main Island at Kilindoni for shopping to catch-up to the current fashion trends; thus, they usually lacked time to mend their fishing nets. Apart from fencing, the elderly men who continued with cultivation also opted for surveillance strategy whereby temporary palm huts were built at Mchanganyuma for them to spend daylight hours there to watch over their crops from damage and theft (Interview 13, 2010).…”
Section: The "Cultivable Land" Narrativementioning
confidence: 99%
“…However, if women's engagement in the value chain reduces their time available to contribute to care and feeding practices of children this may have detrimental impacts on nutrition. For example, a study in Tanzania attributed poor infant nutritional status to reductions in breastfeeding rates which occurred following an intervention which led women to become involved in fisheries activities soon after giving birth (Moshy et al, 2013).…”
Section: Accessmentioning
confidence: 99%